The Conformity of Qualitative Characteristics of Financial Reporting of the Universities of Medical Sciences with Public Sector Accounting Standards - Z. Pourzamani; D. Moinian (حسابداری سلامت, 2015)
Introduction: The quality of the information provided in the public sector is of a high importance due to the specific purpose of reporting. Presenting reliable, complete, and timeliness information of the activities in the governmental sector by using desirable public sector accounting system provides a better opportunity for people's monitoring on the offering of governmental services, transparency, improving the performance of the governmental sector, and finally, reforming the public sector. Method: The present research is applied in terms of purpose, and it is a descriptive survey. The data have been collected through a researcher-made questionnaire including 40 questions. The statistical population of the research include 104 financial and budget managers of the Universities of Medical Sciences, and the related experts in the Ministry of Health and Medical Education. The statistical methods for analyzing the data are One-sample t-test and Binomial test. In order to calculate and analyze the above-mentioned data, Excel Software Version 2010 and SPSS Software Version 18 have been used. Results: The qualitative characteristics of the information provided in the financial reports of the Universities of Medical Sciences conform to the public sector accounting standards both regarding the content (including the predictive value, feedback value, representational faithfulness, neutrality and completeness) and the way of presenting information (including comparability, understandability and timeliness). Conclusion: According to the results of the present research, the chief officers of the Ministry of Health and Medical Education can conform to the accounting standards of the public sectors by a little review and slight changes in the way of reporting and presenting the financial statements, but it is necessary to consider the characteristics related to the content of information more than before.